Pharmaceutical Strategies for Stabilizing Drug Nanocrystals - Yang, Hyerim; Kim, Hyeongmin; Jung, Sumin; Seo, Hyeyeon; Nida, Shofa K.; Yoo, Seung-Yup; Lee, Jaehwi (Current Pharmaceutical Design, 2018)
Background: Nanocrystallization technologies have been widely studied in recent years, as the formulation of drug nanocrystals solves problems of poor drug solubility and bioavailability. However, drug nanocrystals in the size range of 1–1000 nm usually need to be accompanied by stabilizers, such as polymers or surfactants, to enhance their stability. Despite their simplicity, improved dissolution rate, and enhanced bioavailability, the limited stability of nanocrystal formulations has prevented further development. Objective: The most effective way to handle this instability is to use stabilizers. This paper reviews various factors to consider for the production of stable drug nanocrystals and provides suggestions to overcome the problems associated with instability, such as aggregation and Ostwald ripening. Through various examples of stabilizers acting via electrostatic and steric stabilization, this review highlights the scope of enhancing the stability of drug nanocrystals. Conclusion: Studies on stabilizers used in the production of drug nanocrystals are ongoing; various factors, such as the effect of zeta potential on the stability of drug nanosuspensions, have already been revealed. However, it is necessary to determine the most appropriate stabilizer experimentally based on the various mechanisms and factors have been reviewed since the possible interactions between each drug and stabilizer are diverse.
Keywords: nanosuspension